Teaching about European Socialism to Rethink our Societies - Kott, Sandrine (Radical Teacher, 2023)
The following text is a review of different experiences teaching socialism as a way to think critically about the world. Starting from the original 19th-century texts, it discusses the way in which socialists drew the contours of a better, more just, less unequal, less oppressive society, as well as the contradictions and limits of these projects, in particular by looking at the recent choices that socialist leaders have made in Europe. Working with a recent historiography that is more interested in practices and implementations than in theoretical debates, the essay also reflects on the successes obtained but also on possible drifts and failures. Socialism as it has been conceived and practiced in the wake of European industrialization does not offer a ready-made solution to the problems of our time, but the plurality of socialist projects and practices opens avenues for rethinking our world.